Irrigation and lithothamnium fertilization in bell pepper cultivated in organic system - Adão W. P. Evangelista; André R. M. de Sá; José Alves Júnior; Derblai Casaroli; Wilson M. Leandro; Jorge L. M. de Souza (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT For proper plant growth and achievement of satisfactory yield, it is essential to replenish water and nutrients, in the right amount and time. Therefore, the aim of this study was to evaluate the effects of soil water potential and lithothamnium doses on the growth and yield of bell pepper fruits in an organic production system. The experimental design was randomized blocks in a 5 x 4 factorial scheme, with four replicates. The treatments were five lithothamnium doses (0, 0.5, 1, 2 and 4 g dm-3) and four soil water potentials (-6, -24, -42 and -60 kPa). Increasing lithothamnium doses and irrigations based on increasing soil water potentials produced linear increase in plant growth and fruit production. The maximum economic efficiency of the lithothamnium fertilizer was obtained with the application of 0.54 g dm-3, corresponding to the fruit yield of 491.26 g plant-1. More frequent irrigations favor the increase in growth and yield of bell pepper in organic system.